Clonal analysis reveals high rate of structural mutations in fimbrial adhesins of extraintestinal pathogenic Escherichia coli - Scott J. Weissman; Sujay Chattopadhyay; Pavel Aprikian; Mana Obata‐Yasuoka; Yuliya Yarova‐Yarovaya; Ann E. Stapleton; William Ba‐Thein; Daniel E. Dykhuizen; James R. Johnson; Evgeni V. Sokurenko (2005)
Type 1 fimbriae of Escherichia coli mediate mannose-specific adhesion to host epithelial surfaces and consist of a major, antigenically variable pilin subunit, FimA, and a minor, structurally conserved adhesive subunit, FimH, located on the fimbrial tip. We have analysed the variability of fimA and fimH in strains of vaginal and other origin that belong to one of the most prominent clonal groups of extraintestinal pathogenic E. coli, comprised of O1:K1-, O2:K1- and O18:K1-based serotypes. Multiple locus sequence typing (MLST) of this group revealed that the strains have identical (at all but one nucleotide position) eight housekeeping loci around the genome and belong to the ST95 complex defined by the publicly available E. coli MLST database. Multiple highly diverse fimA alleles have been introduced into the ST95 clonal complex via horizontal transfer, at a frequency comparable to that of genes defining the major O- and H-antigens. However, no further significant FimA diversification has occurred via point mutation after the transfers. In contrast, while fimH alleles also move horizontally (along with the fimA loci), they acquire point amino acid replacements at a higher rate than either housekeeping genes or fimA. These FimH mutations enhance binding to monomannose receptors and bacterial tropism for human vaginal epithelium. A similar pattern of rapid within-clonal structural evolution of the adhesive, but not pilin, subunit is also seen, respectively, in papG and papA alleles of the di-galactose-specific P-fimbriae. Thus, while structurally diverse pilin subunits of E. coli fimbriae are under selective pressure for frequent horizontal transfer between clones, the adhesive subunits of extraintestinal E. coli are under strong positive selection (Dn/Ds > 1 for fimH and papG) for functionally adaptive amino acid replacements.